Transnational Anti-Communism and the Cold War Agents, Activities, and Networks - Dongen, Luc van.; Roulin, Stéphanie; Scott-Smith, Giles; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
How was anti-communism organised in the West? This book covers the agents, aims, and arguments of various transnational anti-communist activists during the Cold War. Existing narratives often place the United States – and especially the CIA – at the centre of anti-communist activity. The book instead opens up new fields of research transnationally.
Keywords: Social history; Civilization-History.; World history; World politics; History, Modern; United States-History.; Social History; Cultural History; World History, Global and Transnational History; Political History; Modern History; US History